PERLINDUNGAN TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM (ABH) MELALUI PEMBIMBING KEMASYARAKATAN - Adrian Sofyan (SOSIOHUMANITAS, 2020)
Law of the Republic of Indonesia No. 3 of 1997 on Children's Justice, in 2012 was replaced with Law of the Republic of Indonesia No. 11 of 2012 on the Child Criminal Justice System, this brought fresh wind to the legal problems faced by children. It is hoped that with the presence of Law Number 11 of 2012 can help solve various problems of children facing the law, which increasingly, increasing with a wide range of cases. Correctional Center which is a correctional technical implementation unit that carries out the duties and functions of community research, mentoring, supervision, and mentoring". In this case Bapas has the duty and function to carry out assistance to the child facing the law from the moment in the investigation process until the implementation of the judge's decision. As a human being, a child as a member of society, also has the right to be protected and respected and not treated arbitrarily by more mature people especially in this case by society, which is expected to help supervise children facing the law. The participation of Community Guidance is necessary to assist the child in bridging the needs of children who are dealing with the law. In the process of making news events in the Police, for example, in addition to being accompanied by parents and legal advisors, it is also necessary to be accompanied by the Chairman of The Neighbor's Harmony or the Chairman of The People's Harmony who knows the attitude and practice of the child in the middle of his community. The results showed that the involvement of community advisers who were not optimal, could lead to the rights of children to get justice and protection could not be fulfilled. The child will again commit a violation of the law, if the child returns to the original environment when the child commits a crime. So in addition to parental supervision, mentoring by community supervisors to children who have not committed a crime or who have finished coaching in the Special Child Coaching Institute, needs to be improved, especially the role of Community Guidance towards ABH.